2017
DOI: 10.1016/j.fuel.2016.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Improving the properties of high volatile coking coals by controlled mild oxidation

Abstract: Four bituminous coals of the same rank but with different thermoplastic properties were oxidized at 40 and 50 ºC for one month. The chemical changes due to oxidation were studied by applying Gieseler plastometry, the free-swelling index (FSI), thermogravimetric analysis and Fourier transform infrared spectroscopy (FTIR). In general, oxidation at 50 ºC produced a greater impairment of coking properties, the different responses to oxidation depending on the parent coal. The main effects caused by oxidation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
5
0
1
Order By: Relevance
“…The pycnometer density is determined in a similar way to true density: however, the sample analysed is not pulverised. The values of pycnometer density varied from 1729.3 to 1903.1 kg m −3 and were comparable to those obtained by Vega et al [32] by applying a helium pycnometer.…”
Section: Physical Propertiessupporting
confidence: 88%
“…The pycnometer density is determined in a similar way to true density: however, the sample analysed is not pulverised. The values of pycnometer density varied from 1729.3 to 1903.1 kg m −3 and were comparable to those obtained by Vega et al [32] by applying a helium pycnometer.…”
Section: Physical Propertiessupporting
confidence: 88%
“…8) On the contrary, it was reported that coking property of coal having high caking properties can be improved by proper weathering and deterioration of caking property because the coal with excessive caking properties tends to becomes fragile coke with highly porous structure. [9][10][11][12] For example, Vega et al 12) investigated that the changes of properties of coal after weathering processing and coke derived from processed coal. In that paper, 4 high MF coals were processed in dryer machine at 40 or 50 degrees Celsius with the air atmosphere within 40 days.…”
Section: (Received On December 3 2018; Accepted On February 15 2019)mentioning
confidence: 99%
“…Kandungan zat tebang yang sangat tinggi memiliki kandungan hidrogen dan rasio H/C yang relatif tinggi [1,3,25]. Hal tersebut akan menyebabkan batubara akan lebih bersifat reactive sehingga akan menyebabkan maksimum fluiditas yang tinggi [26,27]. Untuk itu harus diperlukan suatu proses agar syarat sebagai batubara coking dapat sepenuhnya terpenuhi, misalnya dengan proses blending.…”
Section: Hasil Dan Diskusiunclassified